2016
DOI: 10.1159/000447512
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Therapy of Esophageal Cancer

Abstract: Esophageal cancer (EC) is the fourth leading cause of cancer death in China. Despite a lot of advances in diagnosis and therapy, the survival rate of patients with EC is low. There is urgent need for a variety of methods and techniques to improve the survival time and alleviate the lesions of EC. Nowadays, alternative and less invasive approaches to the treatment of ECs are being identified. Here, we review several main interventional methods at different stages of EC, including endoscopic resection, stent pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…SEMS placement is used widely for the palliative treatment of unresectable malignant esophageal stricture [ 1 3 ]. Major complications such as hemorrhaging, perforation, fistula, a fever, and aspiration pneumonia occurred in 22% of subjects [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…SEMS placement is used widely for the palliative treatment of unresectable malignant esophageal stricture [ 1 3 ]. Major complications such as hemorrhaging, perforation, fistula, a fever, and aspiration pneumonia occurred in 22% of subjects [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stent selection should be basis on tumor location, operator experience and expected survival [10,15,17]. Stent placement sometimes requires both endoscopic and fluoroscopic guidance [22]. The SEMS should be placed 2cm above and below the neoplastic lesion and dilatation is not necessary.…”
Section: Technique Of Insertionmentioning
confidence: 99%
“…Tumor ingrowth can be decreased by using of covered SEMS, but with an increased rate of stent migration [10,15]. The migration risk increase when the stent is placed across the gastroesophageal junction [22]. Partially covered SEMS help to prevent migration but their removal is sometimes difficult according to high rate of tumor in growth [18,31].…”
Section: Post Procedures Complicationsmentioning
confidence: 99%
“…Esophageal squamous cell carcinoma (ESCC) is a common tumor of the digestive tract. The incidence and mortality of ESCC varies among countries, and China has a high ESCC risk (1,2). Thanks to the development of genetic and molecular biology, pathogenesis of ESCC is now better understood.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that dysregulated miRs might have a role in of tumors development (8). Notably, miR-490-3p has been reported to be associated with the incidence of various types of cancer (1,(9)(10)(11)(12)(13)(14)(15)(16). In the present study, analysis of miRs expression in ESCC tissues and adjacent tissues from The Cancer Genome Atlas (TCGA) database demonstrated that miR-490-3p was significantly lower in ESCC tissues; however, the role of miR-490-3p in ESCC remains unknown.…”
Section: Introductionmentioning
confidence: 99%